برنامج مسرح عرائسي لتنمية السلوكيات البيئية الإيجابية لطفل الروضة كمدخل للحد من التغيرات المناخية في ضوء الاستراتيجية الوطنية 2050 نموذج الجمهورية الجديدة - أبو زيد، شيماء عبدالعزيز محمد; غنيم، مريم يوسف محمد (جامعة أسيوط - كلية التربية للطفولة المبكرة, 2023)
هدفت الدراسة إلى إعداد برنامج مسرح عرائسي لتنمية السلوكيات البيئية الإيجابية لطفل الروضة كمدخل للحد من التغيرات المناخية في ضوء الاستراتيجية الوطنية ٢٠٥٠ نموذج الجمهورية الجديدة. تكونت عينه الدراسة من (۱۰۰) طفلا وطفلة من الأطفال في مرحلة الطفولة المبكرة داخل معهد الدكتور محمد سيد طنطاوي بالتجمع الخامس بالقاهرة الجديدة، من ٥: ٦ سنوات، مقسمين بين ٥٠ مجموعة تجريبية ٥٠ مجموعه ضابطة. أدوات الدراسة: -اختبار ذكاء الأطفال (إعداد إجلال سري (۱۹۸۸). -مقياس السلوكيات البيئية الإيجابية المصور لطفل الروضة (إعداد الباحثتان). -برنامج المسرح العرائسي لتنمية السلوكيات البيئية الإيجابية (إعداد الباحثتان). قد أسفرت نتائج الدراسة: عن تفوق أطفال المجموعة التجريبية على أطفال المجموعة الضابطة في القياس البعدي على المقياس المصور لصالح القياس البعدي للمجموعة التجريبية، تفوق أطفال المجموعة التجريبية في القياس البعدي عن القبلي على المقياس المصور، ثبات درجات أطفال المجموعة التجريبية في القياسين البعدي والتتبعي لتطبيق البرنامج على المقياس المصور مما يدل على بقاء إثر التعلم. Search target to Apuppet theater program to develop the positive environmental Behaviors as an entrance Climate Changes in the light of the the national strategy 2050 the New Republic Model The research sample consisted of (100) male and female children in early childhood at the Dr. Mohamed Sayed Tantawy Institute in the Fifth Settlement in New Cairo, from 5:6 years old, divided into 50 children in an experimental group and 50 children in a control group Study tools:- Children's intelligence test (prepared by Ijlal Sri 1988).- Illustrated positive environmental behavior scale for kindergarten children (prepared by the researcher).- The puppet theater program for developing positive environmental behaviors (prepared by the researcher). The Results of the research: revealed that the children of the experimental group outperformed the children of the control group in the post-measurement on the pictorial scale in favor of the post-measurement of the experimental group, The children of the experimental group excelled in the post-measurement over the pre-measurement on the pictorial scale, The stability of the scores of the children of the experimental group in the post- and follow-up measurements of applying the program on the pictorial scale and verbal card, which indicates the persistence of the learning effect.
Keywords: البرامج المسرحية -- السلوكيات البيئية -- أطفال الروضة -- الاستراتيجيات الوطنية